III-V material solar cells for space application - Torchynska, T.V.; Polupan, G.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The present paper is a review of current situation in space solar cell engineering. The comparison of the Si and III-V solar cell performances, as well as their parameter variation with temperature rise, radiation treatments and improving design were analyzed. The modern directions of the space solar cell development and international space projects, applied new types of solar cells, were discussed as well.